WORKSHOP PENGOLAHAN DATA MENGGUNAKAN SPSS BAGI MAHASISWA UNIVERSITAS PENDIDIKAN MANDALIKA - Baiq Rika Ayu Febrilia; Dwi Utami Setyawati (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Community service entitled workshop on data processing for students using SPSS aims to assist students in using the SPSS application so that they can do a data processing quickly and accurately, and teach students how to read the results of the analysis and conclude the output of SPSS. The subjects in this service are students of mathematics education study programs, Mandalika education universities consisting of 11 female students, and four male students. The method used in this service is there are two stages, namely the preparation stage of the scene that identifies the problems that arise in the subject and the stage of the implementation of the stage of giving material to the issue, either lecture or direct practice. The results of community service stated that the beginning of the student meeting had several obstacles, such as inputting data from excel to SPSS, misplaced in attaching data, and reading the results of analysis from SPSS output. However, after being guided by the service team, students respond well as following the steps in using SPSS. So, it can say that this service goes according to the target of the service team.